Electrophoretic displays for IR emissivity modulation and temperature control. Issue 1 (5th December 2022) - Chrun, Jonathan; Da Silva, Alexandre; Vancaeyzeele, Cédric; Vidal, Frédéric; Aubert, Pierre-Henri; Dupont, Laurent
Abstract : The first electrophoretic display capable of IR dynamic modulation for temperature control was fabricated and evaluated. The apparent temperature observed with IR cameras was modulated by 4 °C in LWIR and by 10 °C in MWIR. Abstract : The fabrication of an electrophoretic display operating in the infrared range (MWIR and LWIR) for temperature regulation is described. For this purpose, aluminium-doped zinc oxide (AZO) nanoparticles were the electrophoretic particles of choice. The infrared absorption properties of AZO NPs arise from their localized surface plasmon resonance which results in specific wavelength absorption, depending on the size, shape and aluminium doping ratio. These AZO nanoparticles were then formulated to be incorporated into electrophoretic inks with Isopar L as the solvent. To confer good electrophoretic mobility to AZO, a charge control agent Span 80 was added. Once formulated, these inks were used in an electrophoretic cell that displays a dynamic IR emissivity modulation feature. The cell architecture consists of an electrophoretic ink confined between an asymmetric interdigitated electrode array and an infrared-transparent cover. The final devices present emissivity variations up to Δ ε 30% in IR-II (MWIR) and Δ ε 8% in IR-III (LWIR).